1992
DOI: 10.1210/endo.131.6.1446607
|View full text |Cite
|
Sign up to set email alerts
|

A cryptic peptide (160-169) of thyrotropin-releasing hormone prohormone demonstrates biological activity in vivo and in vitro.

Abstract: TRH is synthesized as a precursor peptide containing five copies of the sequence Gln-His-Pro-Gly, QHPG, flanked by paired basic amino acids, and linked by other peptides. We tested one cryptic peptide, PPT (160-169, SFPWMESDVT), as a possible physiological regulator of pituitary activity in vivo. Male rats were cannulated (jugular) and received a single dose of either PPT or TRH (10(-8)-10(-6) M). PPT caused no consistent effects on either TSH or PRL secretion, while TRH stimulated the secretion of both hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In the TRH Ϫ͞Ϫ mice, five copies of the TRH progenitor sequence and its intervening peptides were simultaneously disrupted. Although several studies have shown biological activities of the intervening peptides on pituitary hormones, the results are still contradictory (36)(37)(38)(39)(40), and pathological roles of the intervening peptides in development of hyperglycemia of the TRH Ϫ͞Ϫ mice remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In the TRH Ϫ͞Ϫ mice, five copies of the TRH progenitor sequence and its intervening peptides were simultaneously disrupted. Although several studies have shown biological activities of the intervening peptides on pituitary hormones, the results are still contradictory (36)(37)(38)(39)(40), and pathological roles of the intervening peptides in development of hyperglycemia of the TRH Ϫ͞Ϫ mice remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…2) Authentic Ps4 is released from hypothalamic neurons in vitro (4,5), and substantial amounts of Ps4 are found in the hypophysial portal blood (26). 3) Synthetic Ps4 has been shown to potentiate TRH-induced TSH release (6,8) and to increase TSH and PRL gene expression (27,28 (3-10), whereas the [Tyr 0 ]Ps4 analog is resistant to enzymatic degradation (6). Moreover, addition of a Tyr residue at the N-terminus of Ps4 has been shown to increase the binding affinity of the peptide (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was demonstrated that Ps4, like TRH, induces a dose-dependent increase of ß-TSH mRNA content in intact animals, primary pituitary cell cultures and in a heterologous TSH expression assay [7,8]. Recently, another group has revealed the biological importance of Ps4 in the dorsal motor nucleus of the vagus, a region where TRH plays a pivotal role to activate directly neurons leading to the stimulation of vagai outflow to the stomach and gastric function.…”
Section: Introductionmentioning
confidence: 99%